Master’s programs in midwifery education in South Asia: organizational frameworks, competency goals, and learning outcomes - Kumari, Ritu; S., Karthika; Mundotiya, Meenakshi; Kalyani, B.; Umar, Mohammed; A., Jenifar Monisha; N. R., Deepa; Suhashini; Singh, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
South Asia continues to experience a disproportionate burden of preventable maternal and neonatal morbidity and mortality, while countries in the region are simultaneously accelerating midwifery reforms through advanced education pathways. Over the past decade, several South Asian countries have introduced or proposed master’s-level midwifery programs, often aligned with international confederation of midwives (ICM) competencies and world health organization (WHO) quality standards. This review synthesizes the current landscape of master’s programs in midwifery education across South Asia (Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, Sri Lanka), examining organizational frameworks, competency goals relative to global benchmarks, and evidence on learning outcomes, implementation challenges, and policy alignment. A systematic review of peer-reviewed literature, national regulations, policy documents, and program webpages (2010-August 2025) was conducted, prioritizing authoritative sources including ICM, WHO, UNFPA, national acts, council guidelines, and university curricula. Data extraction focused on program typology, credit requirements, theory-practice ratios, competency frameworks, assessment modalities, and documented outcomes. Findings indicate regional convergence around ICM global standards for midwifery education (2021) and ICM essential competencies (2024), including minimum program durations (36 months direct-entry; 18 months post-nursing) and recommended theory/clinical ratios (40%/≥50%). India’s midwifery reforms (Guidelines on midwifery services, NPM educator programs, NNMC act 2023) provide a scalable national framework; Nepal offers a dedicated M. Sc. in Midwifery at Kathmandu university; Bangladesh is developing in-country master’s provision; and Pakistan emphasizes MSN tracks with maternal-neonatal specialization. Establishing a regional master’s archetype anchored in ICM/WHO standards, supported by robust clinical partnerships, OSCE-based assessment, and research-to-policy integration, can accelerate safe, respectful, and evidence-based maternity care across South Asia.